2013
DOI: 10.9790/2380-0653644
|View full text |Cite
|
Sign up to set email alerts
|

Soil Test Based Fertilizer Prescriptions Through Inductive Cum Targeted Yield Model for Transgenic Cotton on Inceptisol

Abstract: Studies on Soil Test Crop Response based Integrated Plant Nutrition System (STCR -IPNS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…Comparing the contribution from soil vs fertilizer, greater contribution was recorded from the fertilizer than from the soil. Above results coincide with the report on fertilizer contribution towards aggregatum onion by (Sugumari et al, 2021) and (Katharine et al, 2013) on cotton.…”
Section: Fertilizer Potassium (Fk 2 O)supporting
confidence: 92%
“…Comparing the contribution from soil vs fertilizer, greater contribution was recorded from the fertilizer than from the soil. Above results coincide with the report on fertilizer contribution towards aggregatum onion by (Sugumari et al, 2021) and (Katharine et al, 2013) on cotton.…”
Section: Fertilizer Potassium (Fk 2 O)supporting
confidence: 92%
“…Furthermore, a lower targeted yield was more easily achieved than the higher ones. Similar findings were also reported by [61]. The maximum HI was recorded in STCRTY1 (44.30%), which differed significantly from CK (37.55%) and FP (37.51%).…”
Section: Yield and Production Efficiencysupporting
confidence: 89%
“…The data clearly revealed the fact that the fertilizer N, P 2 O 5 and K 2 O requirements decreased with increase in soil test values and increased with increase in yield targets. Similar finding also reported in cotton by Katharine et al (2013).…”
Section: Resultssupporting
confidence: 91%
“…The average nutrient requirement of preseasonal sugarcane ratoon was found to be 1.56, 0.58 and 1.64 kg t -1 of N, P 2 O 5 and K 2 O respectively. Similarly Katharine et al,(2013) also reported that the nutrient requirement to produce one quintal (100 kg) of seed cotton was 4.43 kg of N, 2.20 kg of P 2 O 5 and 4.83 kg of K 2 O.The percent contribution of nutrients from soil and fertilizers were found to be 37.65 and 34.83 for N, 85.88 and 36.99 for P 2 O 5 and 19.82 and 30.80 for K 2 O . Similarly the percent contribution of N, P 2 O 5 and K 2 O from FYM was 11.83, 10.88 and 12.24 respectively.…”
Section: Resultsmentioning
confidence: 99%